The Triune God : Systematics, Volume 12 - Lonergan, Bernard J. F. (Book collections on Project MUSE., 2007)
"Buried for more than forty years in a Latin text written for seminarians at the Gregorian University in Rome, Bernard Lonergan's 1964 work on systematic theological, De Deo trino: Pars systematica, is presented here for the first time in a facing-page edition that includes the original Latin along with a precise English translation. De Deo Trino, or The Triune God, continues a particular strand in trinitarian theology, namely, the tradition that appeals to a psychological analogy for understanding trinitarian processions and relations."--Jacket.